Bibliometric Analysis of Evaluation in Physical Education: A Study Based on The Scopus Database From 2013 to 2023 - Sefri Hardiansyah; Nurlan Kusmaedi; Amung Ma'mun; Herman Subarjah (Yayasan Keluarga Guru Mandiri, 2024)
Evaluation in physical education provides information about the extent to which physical education objectives have been achieved and ensures that all processes have been carried out correctly. This study aims to investigate trends in evaluation research in physical education based on the Scopus database from 2013 to 2023. This is expected to provide an overview of the latest developments in evaluation research in physical education and to illustrate future research opportunities. Based on a search of the Scopus database through the Publish or Perish application with two title words,